2016
DOI: 10.4274/tjo.57778
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ocular Surface Health in Patients with Obstructive Sleep Apnea Syndrome

Abstract: Objectives:To evaluate ocular surface health in obstructive sleep apnea syndrome (OSAS) and to investigate the tendency of these patients toward dry eyes.Materials and Methods:Fifty patients who underwent polysomnography and were diagnosed with OSAS and 50 normal control subjects were compared with respect to ocular surface disease index (OSDI), Schirmer I test and tear film break-up time (TBUT) values.Results:Patients were grouped as mild (n=15, 30%), moderate (n=15, 30%) and severe (n=20, 40%) according to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…The results of closed-eye studies and elevated tear matrix metaprotease-9 in DED suggest that patients with DED may have more inflammatory processes than controls during sleep. 54,55 Patients with DED have a high prevalence of obstructive sleep apnea, [56][57][58][59] and its therapy, continuous positive airway pressure, may worsen DED. 60 Air conditioning and sleep position 61,62 also may worsen DED.…”
Section: Eyes Are Disturbed At Night With Dedmentioning
confidence: 99%
“…The results of closed-eye studies and elevated tear matrix metaprotease-9 in DED suggest that patients with DED may have more inflammatory processes than controls during sleep. 54,55 Patients with DED have a high prevalence of obstructive sleep apnea, [56][57][58][59] and its therapy, continuous positive airway pressure, may worsen DED. 60 Air conditioning and sleep position 61,62 also may worsen DED.…”
Section: Eyes Are Disturbed At Night With Dedmentioning
confidence: 99%
“…Highlighted as a multifactorial disease with complex ocular disorders involving diverse findings and symptoms resulting from various origins [27] is important to monitor patients with OSA for possible relating eye manifestations and being aware of the association. Previous studies have reported that early diagnosis of DED has clinical relevance in OSA patients due to greater inclination to develop DED [28,29]. Identification of patients with ocular injuries is important, as these patients are at increased risk of developing alteration of the ocular surface anatomy and further ocular manifestations of which floppy eyelid syndrome (FES), nonarteritic anterior ischemic optic neuropathy, glaucoma and central serous retinopathy imbed [30,31].…”
Section: Resultsmentioning
confidence: 99%
“…Shift work primarily results in sleep disturbances, with acute symptoms including difficulty falling asleep, reduced sleep duration, and somnolence in the following days [ 11 ]. Previous studies have reported that sleep disorders and DED interact with each other [ 13 16 ]. Poor sleep quality has been reported in 45% of young and middle-aged DED office workers [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sleep duration of ≥9 h/d has been found to be a protective factor for dry eye symptoms [12]. Patients with obstructive sleep apnea syndrome (OSAS) have a tendency to develop dry eye [13]. In addition, the prevalence of sleep and mood disorders was higher in patients with DED than in patients with other ocular surface diseases, and the severity of sleep quality was correlated with the grade of DED [14,15].…”
Section: Introductionmentioning
confidence: 99%